2018
DOI: 10.18520/cs/v115/i10/1963-1969
|View full text |Cite
|
Sign up to set email alerts
|

The Host Range of Multi-Host Endophytic Fungi

Abstract: Mature leaves of 224 angiosperm plant species belonging to 60 families and growing in Andaman Islands, and the states of Arunachal Pradesh, Kerala and Tamil Nadu were sampled for the presence of endophytic fungi. Fungal genera such as Alternaria, Arthrinium,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 23 publications
3
18
0
1
Order By: Relevance
“…The broad host range as well as the high colonization frequency of Xylariales observed in the present study is noteworthy and corroborated with Yu et al [16]. It has also been proven several times that members of Xylariales establish an endophytic association with taxonomically unrelated plants, which are geographically isolated [26][27][28][29][30]. Indeed the host acquisition ability of Xylaria as an endophyte is high, and it has been isolated from plants belonging to 3 divisions (including liverworts and higher plants) and occurring on 2 continents [31].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The broad host range as well as the high colonization frequency of Xylariales observed in the present study is noteworthy and corroborated with Yu et al [16]. It has also been proven several times that members of Xylariales establish an endophytic association with taxonomically unrelated plants, which are geographically isolated [26][27][28][29][30]. Indeed the host acquisition ability of Xylaria as an endophyte is high, and it has been isolated from plants belonging to 3 divisions (including liverworts and higher plants) and occurring on 2 continents [31].…”
Section: Discussionsupporting
confidence: 90%
“…Indeed the host acquisition ability of Xylaria as an endophyte is high, and it has been isolated from plants belonging to 3 divisions (including liverworts and higher plants) and occurring on 2 continents [31]. In our investigations in the forests near the locations from which the lichens were col- lected in the present study, we isolated species of Xylaria as foliar endophytes [30]. Xylaria apiculata, occurring as endolichenic fungus in Arthonia in the present study, exhibits both decomposer and endophytic life strategies in tropical forests [28].…”
Section: Discussionmentioning
confidence: 70%
“…It is true that many cultivable endophytic taxa are known to have broad host ranges (e.g. Arnold and Lutzoni, ; Suryanarayanan et al ., ), thus one could argue that an understanding of endophyte biodiversity does not hinge on thorough sampling of potential host taxa. However, we note that, in the majority of multivariate studies of endophyte biogeography, host taxon is a supported predictor of assemblage variation (Griffin et al ., ; Kivlin et al ., ) – albeit a sometimes modest one (Vincent et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…They are also known to produce pharmaceutically important secondary metabolites and enzymes (Shweta et al, 2010;Kusari et al, 2013;Kaushik et al, 2014;Kumara et al, 2014;Nagarajan et al, 2014;Uzma et al, 2019) and phytohormones (Bilal et al, 2017(Bilal et al, , 2018. In the past few decades, it became obvious that endophytes could be isolated from every plant studied (Strobel and Daisy, 2003;Hardoim et al, 2015;Suryanarayanan et al, 2018a;Giauque et al, 2019). These analyses showed that many attributes of endophytes, in particular their universal occurrence, sustained presence in plants, non-pathogenic nature, ability to enhance the biotic and abiotic stress tolerance of their plant hosts (Rodriguez et al, 2009), increase access to soil nutrients and increase the plant yield (White et al, 2019;Xia et al, 2019) project them as candidates holding high promise for use in crop improvement.…”
Section: Introductionmentioning
confidence: 99%